PENERAPAN METODE TARGET COSTING DALAM PERHITUNGAN HARGA POKOK PRODUKSI PADA PEMBUATAN PRODUK INNER CARTON (STUDI KASUS PT. MAKMUR MULTI MITRA) - Diba, Fitri Farah; Hidayati, Cholis (Universitas 17 Agustus 1945 Surabaya, 2018)
ABSTRACTIn this study using descriptive qualitative research methods. Case study at PT. Makmur Multi Mitra which is engaged in the manufacture of inner carton products operating in Surabaya and research only focuses on making inner cartons for the period 2015. The data source used in this study is internal data sources namely data obtained from within the company consisting of primary data and secondary data. Management of PT. Makmur Multi Mitra has determined the price of its inner carton products of Rp. 5,000.00 per pcs and the price is lower than its competitors. From the selling price the company wants a profit of Rp. 1,500.00 per pcs but after analyzing the manufacturing costs which include the cost of raw materials, direct labor costs, and overhead costs it turns out that the actual profit obtained is only Rp. 1,369.00 because the actual cost of production is Rp. 3,631.00. Therefore, the authors provide a solution to reduce production costs by offering three scenarios and one of the scenarios suggested to be implemented is to make changes by replacing direct raw materials used by the company with slightly lower quality raw materials (KW II) while replacing materials for engineering coating of prints to reduce manufacturing costs to Rp. 3,465.00 per pcs inner carton or smaller Rp. 35.00 from the target cost and get a profit of Rp. 1,535.00 per pcs. Keywords: Target Costing, Cost of Production, Costs, Selling Price